The microanatomy of saphenous and popliteal arteries in angora rabbit - Sadullah Bahari; Vural Özdemir (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this study was to show macroanatomical conformation of saphenous and popliteal artery in Angora Rabbits and to compare results with other domestic animals. Material and method: fn this study 10 adult Angora Rabbits of both sexes were used. The animals were sacrtficsd by ordinary method and injected colored latex by means of the abdominal aorta. Results: Giving the highest (descending) genicular artery, saphenous artery coursed superficially to medial surface of the leg and then gave off lateral and medial plantar arteries on the one of fourth distal surface of tibia. Highest genicular artery had two branches which were called superficial and prolund. First branch supplied to fascia and subcutan tissue on the medial surface of the stifle joint. Second branch gave branches which supplied to femoropatellar joint and cranial region of the stifle joint. Flexor tendons and their tendovagina which passed through plantar surface of tarsal joint and this joint were mostly supplied by lateral plantar artery. Alter giving branches to heel plexus, medial plantar artery divided into profund and superficial ramit. First branch joined arcuate artery lor composing of deep plantar arch. Second branch initially supplied to sole and then gave off plantar common digital arteries to supply to digits. After giving lateral proximal and medial proximal and middle genicular, sural and caudal tibial arteries, popliteal artery continued as cranial tibial artery. Caudal tibial artery vascularized popliteal and some llexor muscles which placed on caudal region of calf. Cranial tibial artery gave medial distal genicular and recurrens crania! tibial arteries and nutrient artery to the libula behind crus and then divided into proximal and distal branches. These branches reached front of the crus by perforating interosseal membran. After giving branches which supply extensor muscles on the lateral surface of tibia, proximal branch reached upper surface of foot as superficial ramus and composed of dorsal common digital arteries. Distal branch initially gave nutrient artery of the tibia and then passed front of the crus and continued its course as dorsal pedal artery to the tarsal joint. Conclusion: The findings o( our study suggest that the origin, movement and vascularization area of saphenous and popliteaı artery ot this stsecies demonstrated closely resembles to that of the New Zealand white rabbits.